Intra-adrenal Paraganglioma and Paraaortic Paraganglioma in 15 Years Old Boys - Butarbutar, Christine Rosalina; Maker, Luh Putu Iin Indrayani; Sumadi, I Wayan Juli; Winarti, Ni Wayan; Ariyanta, Kadek Deddy; Asih, Made Widhi (Majalah Patologi Indonesia, 2024)
Intra-adrenal paraganglioma (also called pheochromocytoma) is a chromaffin cell tumor that arises in the adrenal medulla and produces excess catecholamines. Paraganglioma can also be located in the extra-adrenal area. The incidence rate of intra-adrenal and extra-adrenal paraganglioma is about 1 case per 2.500-6.500 population, highest incidence at 40-50 years old, and distribution is the same in males and females. Intra-adrenal paraganglioma in pediatrics is more familial, bilateral, multifocal, and malignant. In children, the incidence rate of these tumors was 8.86%, the ratio of boys to girls was 2:1, and the average age of 11. This article reports a case, of a 15 years old boy with severe headaches, recurrent seizures, and a hypertension crisis (143/103-220/110 mmHg). MSCT scan of abdominal showed solid mass heterogeneous with central necrotic multiple in the supero-anterior of the left and right kidneys and on the right anterolateral aorta as high as CV L2, impressive adrenal gland mass and extra-adrenal, suspect pheochromocytoma. Performed surgery, routine histopathological examination, and Immunohistochemistry. Macroscopic examination showed an oval round shape mass of left and right adrenal tumors as well as the paraaortic, a smooth outer surface of the capsular, with yellowish brown color mass tumor at cut surface, supple consistency. Microscopic examination showing adrenal gland and paraaortic tissue with fibrous capsule contains proliferation of neoplastic cells forming a nested alveolar (Zellballen) pattern with a round oval to polygonal cells, granular eosinophilic cytoplasm, round oval nuclei, surrounded by sustentacular cells. Chromogranin A and S-100 are positive. The case was concluded by clinical findings, histopathological, and immunohistochemistry as intra-adrenal paraganglioma and paraganglioma of paraaortic.